Issues in contemporary Christian thought : a Fortress introduction - Olson, Duane (Minneapolis, MN : Fortress Press, 2011)
"Duane Olson's new textbook uniquely focuses on the central points at issue in contemporary Christian reflection. Olson's clear and concise overview roots contemporary questions firmly in Christian responses to the Enlightenment. This allows Olson to unfold those questions as bequeathed by modernity and to show how the radical reframing of the current period actually builds on the diversity of those lingering concerns.Olson discusses the range of contemporary opinions, their rationales, and what's at stake. He illustrates these alternate frameworks as they play out in central concerns over the being of God in relation to the universe, how to understand the figure of Christ today, and the distinctively new notions of being human. Olson's text includes reflection and research questions, suggestions for further reading, and a glossary" -- Publisher description.
Setting the stage : Christianity and the developments of modernity -- Surveying the field : options in contemporary Christian thought -- God and cosmology -- Christ and history -- Heaven, hell, and anthropology -- Christianity and other religions -- Christianity and feminism -- Christianity and homosexuality -- Christianity and the natural environment.
Includes bibliographical references (p. 249-262) and index.
Keywords: Christian philosophy; Christianity and culture